Disease Duration and Stage Influence Bone Microstructure in Patients With Primary Biliary Cholangitis. (25th March 2018) - Schmidt, Tobias; Schmidt, Constantin; Schmidt, Felix N; Butscheidt, Sebastian; Mussawy, Haider; Hubert, Jan; Hawellek, Thelonius; Oehler, Nicola; Barvencik, Florian; Lohse, Ansgar W; Schinke, Thorsten; Schramm, Christoph; et al.
ABSTRACT: Primary biliary cholangitis (PBC) is known to be a major risk factor for osteoporosis reflected by a reduction of bone mineral density (BMD). However, both the extent of the macro‐ and microstructural alterations of bone as well as the causative factors are unknown. We have retrospectively analyzed a total of 96 patients with PBC and 53 healthy controls matched for age, sex, and body mass index. In addition to dual‐energy X‐ray absorptiometry (DXA) measurements at the lumbar spine and hip, high‐resolution peripheral quantitative computed tomography (HR‐pQCT) was used to assess the geometric, volumetric, and microstructural changes of bone at the distal radius and tibia. Furthermore, serum analyses and measures of disease duration and stage including transient elastography were performed. Total, cortical, and trabecular volumetric BMD as well as geometric parameters were significantly reduced in PBC patients. Microstructural analysis revealed a significantly lower cortical thickness ( p  < 0.001) and bone volume per tissue volume ( p  < 0.001) in the radius and tibia but unchanged trabecular number in patients with PBC (radius: p  = 0.42; tibia: p  = 0.12). Multivariate regression models pointed out that disease duration and stage are the primary factors that are independently associated with bone loss in PBC. A subgroup analysis of patients with additional autoimmune hepatitis (AIH) revealed no significant changes in bone structure compared with PBC only. Taken together, PBC patients demonstrate severe alterations in bone microstructure that are positively associated with disease duration and stage. By applying HR‐pQCT in the distal radius and tibia, a combined bone loss syndrome expressed by a predominant decrease in BMD and cortical thickness could be detected. © 2018 American Society for Bone and Mineral Research.